(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Background – Landslide causes loss of human lives and destruction to property all over the world. India is no exception. State of Kerala experiences landslides during monsoon seasons. There is no study at present to evaluate the injuries sustained by victims in Kerala. This study is meant to analyse the pattern of injuries sustained and - 19 persons died from a single – The victim’s age ranged from 3 to 65. Of these 10 in 10 cases (52.63%) forming the major group, blunt injury alone was cause of death in 8 cases (42.11%).